Arahan Peningkatan Pelayanan Air Bersih Distrik Mimika Baru Kabupaten Mimika (Tahun 2017-2037) - Cynthia Octavia Putri; Muhammad Fathien Azmy; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Clean water in human life is one of the most essential needs, so that we need to fulfill it in sufficient quantity and quality. The water needed is water that meets the requirements of clean water, which are qualitative, quantitative, and continual requirements. This study aims to identify the existing conditions of clean water infrastructure, calculate clean water needs for the next 20 years, and arrange the guidance in improving clean water services in the Mimika Baru district of Mimika Regency, Papua Province. The method of collecting data used is observation and literature study. The analytical method used is descriptive qualitative analysis, quantitative analysis, comparative analysis and SWOT analysis. The results of this study show that clean water needs for the New Mimika District increased by 120% in the next 20 years. Meanwhile, guidance for improving clean water services include the development of clean water infrastructure components such as exploration of new water sources, procurement of intake buildings, processing facilities, pre-treatment reservoirs, post-treatment reservoirs, and so on.